Primary Cutaneous B-Cell Lymphoma: Diffuse Large B-cell Lymphoma, Leg Type - Murat, Ayşe; Özercan, İbrahim Hanifi (My University, 2014)
ABSTRACT Primary cutaneous B-cell lymphoma has only recently been recognized as a distinct clinical entity. Primary cutaneous diffuse large B-cell lymphoma of the legs generally occurs in elderly patients, in particular women. A 70-year-old female patient was admitted to our hospital with her nodular erythematous lesions localized on the left thigh. We performed an ultrasound and color Doppler ultrasound as well as computed tomography. This article will discuss the diagnostic and the treatment options and prognosis of primary cutaneous B-cell lymphoma.
Keywords: Genel ve Dahili Tıp; Onkoloji